Social Housing: Basic Consumer Requirements - Irina D. Verevkina (Academia: Архитектура и строительство, 2019)
Social housing exists in all economically developed countries as a form of providing housing to needy categories of citizens. It plays essential role in social and demographical development regulation in the society (the housing availability affects on the number of children in a family and on the existing of children in a family in general). Social housing as well conduce to vanishing such conditions as homelessness. On one hand, the process of development of contemporary architectural decisions for social housing is disrupted either by obsolete regulatory acts and methodical base. On the other hand, the reform of this base does not make the allowance of contemporary state of real estate development. That is why it is needed to make a revision of some acts with due regard for new types of housing; the variances of consumptions' demand for some elements of the flat; further possibilities of architectural decisions supported by innovations in the sphere of engineering design and constructing technologies. The decision of the point, connected with the advance of the architectural qualities and the cost effectiveness of housing could influence positively on the cost of the residential areas. The purpose of this study is to identify the main characteristics of social type of housing among potential tenants for their further consideration at the stage of housing design. The study was conducted by the use of questioning method of citizens who are registered in district administrations of Tomsk as the one with need in social housing. The obtained data allowed to identify the key preferences of potential tenants. Further researches will be aimed at developing recommendations for social housing design in Tomsk.